Епідеміологічні аспекти мікроальбумінурії у хворих на цукровий діабет 2-го типу та артеріальну гіпертензію - Пасєчко, Н. В.; Паньків, І. В. (Clinical Endocrinology and Endocrine Surgery, 2008)
The main object of this article is to determin microalbuminuria (MAU) in 477 persons aged from 19 to 70 years: 118 practically healthy persons, 268 patients with arterial hypertension, 91 patients with type 2 diabetes mellitus (DM) in conjunction with arterial hypertension. The frequency of MAU about practically healthy persons was 4,2%. There was direct dependence between the age of examined persons and the value of urinary albumin. The frequency of MAU in patients with arterial hypertension was 68%. The frequency of MAU increased in patients with duration of arterial hypertension, the high level of diastolic blood pressure and pulse blood pressure. The prevalence of MAU in patients with type 2 DM in conjunction with arterial hypertension was 85,7%. It is considered that dynamics of MAU level is a marker of duration and heaviness of natural history of DM and arterial hypertension.